Cardiorespiratory, metabolic and perceived responses to electrical stimulation of upper-body muscles while performing arm cycling - Zinner, C.; Matzka, M.; Krumscheid, S.; Holmberg, H. C.; Sperlich, B. (Journal of Human Kinetics, 2021)
This study was designed to assess systemic cardio-respiratory, metabolic and perceived responses to incremental arm cycling with concurrent electrical myostimulation (EMS). Eleven participants (24 ± 3 yrs; 182 ± 10 cm; 86 ± 16.8 kg) performed two incremental tests involving arm cycling until volitional exhaustion was reached with and without EMS of upper-body muscles. The peak power output was 10.1% lower during arm cycling with (128 ± 30 W) than without EMS (141 ± 25 W, p = 0.01; d = 0.47). In addition, the heart rate (2-9%), oxygen uptake (7-15%), blood lactate concentration (8-46%) and ratings of perceived exertion (4-14%) while performing submaximal arm cycling with EMS were all higher with than without EMS (all p < 0.05). Upon exhaustion, the heart rate, oxygen uptake, lactate concentration, and ratings of perceived exertion did not differ between the two conditions (all p > 0.05). In conclusion, arm cycling with EMS induced more pronounced cardio-respiratory, metabolic and perceived responses, especially during submaximal arm cycling. This form of exercise with stimulation might be beneficial for a variety of athletes competing in sports involving considerable generation of work by the upper body (e.g., kayaking, cross-country skiing, swimming, rowing and various parasports).